EFECTO DE LA SUSTITUCIÓN DE HARINA DE MAÍZ POR HARINA DE LENTEJITA DE AGUA Lemna minor EN DIETAS BALANCEADAS SOBRE EL RENDIMIENTO PRODUCTIVO DEL PACO Piaractus brachypomus. - NAPUCHI-LINARES, Juvenal (2024)
Due to the importance of diversifying the feed input matrix for aquaculture through low-impact local biomass, the effect of replacing corn flour with Lemnaminor flour in diets for juvenile Piaractus brachypomus was evaluated. Four isoprotein diets were formulated with 0% (T0), 25% (T1), 50% (T2) and 100% (T3) replacement and administered to 240 fish grown at 10 fish m³ for 75 days. Animals were fed 5% of their body weight, twice a day. Weight gain, specific growth rate (SGR), apparent feed conversion (AFC), protein efficiency (PE), hepatosomatic index (HSI) and survival were recorded. The results show that partial replacement (T1–T2) maintained the final biomass (2.45 ± 0.09 kg), TCE (2.60 ± 0.11% d), AAC (1.81 ± 0.06) and EP (2.24 ± 0.05) without differences compared to the control. In contrast, total replacement (T3) reduced biomass by 24%, apparent intake by 20% and increased IHS by 11% (p < 0.05), indicating a higher metabolic load; survival decreased to 90%. It is concluded that replacing up to 50% of corn flour with L. minor flour is zootechnically viable and economically attractive for P. brachypomus fattening, as it maintains productive performance and takes advantage of local biomass with low environmental impact. Higher substitutions require processing or formulation adjustments to avoid growth and welfare penalties.